Стратегічні орієнтири розвитку складових системи соціальної відповідальності бізнесу на підприємствах харчової промисловості. - Кравчук, Ірина; Olena, Popadiuk (Попадюк О.В., Кравчук І.П. Стратегічні орієнтири розвитку складових системи соціальної відповідальності бізнесу на підприємствах харчової промисловості. Вісник Чернівецького торговельно-економічного інституту. Чернівці: ЧТЕІ КНТЕУ, 2020. Вип. IIІ (79). Економічні науки. с. 159-171, 2020)
Relevance of research of socially responsible economic activity of Ukrainian enterprises is exacerbated by the fact that the domestic economic environment has not passed in its historical development the necessary stages, which in Western society have led to an awareness of the importance of the philosophy of social responsibility. More and more obvious is the fact that the reputation of domestic food industry enterprises is increasingly dependent not only on their profitability, share value, product quality, but also on their activity in the field of social responsibility. However, different approaches to the understanding of social responsibility, inconsistency of actions, and lack of purposeful governance mechanisms provide an unstable platform for further implementation of social responsibility principles in the overall strategy of an enterprise. The purpose of the article is research of strategic directions of development of components of the system of social responsibility of business at the enterprises of the food industry. According to the results of comprehensive research, social responsibility has not yet become a part of organizational management in companies, since only half of the companies implementing corporate social responsibility (CSR) policy have a social responsibility strategy (policy), and only a quarter of companies have a budget for implementation of social responsibility programs / activities, and at most companies the search for ideas for CSR programs and development of plans for their implementation is performed by management. At the same time, the main impetus for the implementation of CSR policy is moral considerations, and as the main obstacles to the implementation of CSR policy company representatives name the lack of funds, unstable political situation in the country, imperfection of the legal framework that would contribute to this activity, and tax pressure. Scientific novelty is in the improvement of the theoretical and methodological provisions for ensuring the strategic development of food industry enterprises on the basis of social responsibility. The article identifies the main trends that Ukrainian enterprises should focus on in the area of corporate social responsibility in view of the European integration processes. Practical valueof the obtained results is inbringing to the level of methodological and practical recommendations that allow to increase the efficiency of the activity of domestic enterprises in the context of ensuring the sustainable development. Practical developments are of universal character and can be applied in other areas of business. This topic has the prospect of research in the field of improvement of methodological support for the assessment of the social responsibility system of the enterprises of the food industry.
Keywords: соціальна відповідальність бізнесу; стратегічні орієнтири розвитку ств; підприємства харчової промисловості; корпоративна соціальна відповідальність